Sustainability in the brazilian timber housing virtual market - Victor Almeida-De Araujo; Juliano Souza-Vasconcelos; Sheyla Mara Baptista-Serra; André Luis Christoforo; José Carlos Paliari (Revista Hábitat Sustentable, 2023)
Timber housing is a sustainable bioresource-based alternative to traditional construction with masonry and steel, and recent studies have shown that this sector in Brazil has hundreds of timber housing SMEs. This exploratory study, while analyzing this population, evaluated the profiles available on Instagram®, observing their business strategies and what they have disclosed to clients on sustainability benefits and issues. All the available corporate profiles were surveyed, and a significant sample of about 80% of a sector was compiled, from a market currently formed by over 400 companies. However, about 70% of these Brazilian companies still do not adequately explore sustainability issues in their timber housing products and service, evidencing an incipient scenario. Moreover, there is a clear opportunity to leverage the arguments posted on their Instagram® profiles as an affirmative awareness strategy. Although some justifications were suggested to convince domestic customers to consider timber housing, this virtual market has a lot of room for improvement.